O crime de estupro no brasil: uma análise discursiva do processo de silenciamento da mulher - Venson, Ana Paula Reckziegel (2022)
This research seeks to mobilize the theoretical notions of Pecheutian Discourse Analysis to reflect on the silencing process to which women, victims of the crime of rape, will be subjected. In 2018, more than 66 thousand cases of rape were recorded, which is equivalent to 1 rape every 8 minutes, of which more than 87% of cases occur against women (FBSP, 2019). These data correspond to cases reported to the competent authorities, which, according to estimates, represent only 7.5% of the reality of crimes, as 92.5% of victims fail to report the crime (BUENO, PEREIRA, NEME, 2019). In order to understand this underreporting, the “forms of silences” proposed by Eni Orlandi (2007) were theoretically conceptualized, namely: the founding silence, which exists above all; the constitutive silence, where what is said in one way could have been said in another, behold, it is not possible to say everything; and the local silence that works as censorship, where the sayings and the subjects are regulated. Thinking that both silences and senses are managed (Orlandi, 2007), it is understood that silence can function as a key point for the construction of individual (Rosa, 2018) and collective meanings of memory, of imaginary and ideological formations, that will circulate about the crime of rape, about the victim and about her aggressor. However, these meanings, will be dictated by the dominant ideological formation (Patriarchal and Capitalist), propagated by the Ideological State Apparatuses (Althusser, 1980) Legislative and Legal, responsible for the edition and application of the Criminal Laws that related to the crime of rape, which in a historical-legislative path, have always exercised patriarchal gender violence, regulating the rights (and “duties”), the body and the sexual behavior of women. To compose the corpus of this research, the statements that define the crime of rape and others that, in some way, deal with this crime, the victim and the aggressor, were cut from the Penal Code of 1940. Also, the Brazilian Public Security Yearbooks from 2015 to 2019 were selected, produced by the National Public Security Forum, which present statistics and other information about the occurrence and victims of this sexual violence. These materialities were analyzed discursively, in the light of Pecheux's Discourse Analysis, building a theoretical device, elaborated in a perpendicular movement between theory and mobilization of senses and meanings, originated from the analyzes (Petri, 2013). The analyzes developed in this research lead to the understanding that there is working an ideological, patriarchal and capitalist discourse, which establishes who can be a victim of crime and blames it for its occurrence, imposing on women, including, in an express way, silence about the crime. the crime. Despite this, recent data show that women, in a gesture of resistance to the Patriarchal and Capitalist discourse, have increasingly denounced the occurrence of the crime and, perhaps, giving rise to a hole in this discourse of silencing imposed on women.